DIPLOMACY OF SAUDI ARABIA IN THE SETTLEMENT OF THE DISPUTE OF TIRAN AND SANAFIR ISLAND WITH EGYPT 2016-2017 - Rifki Adha; M. Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research aims as a study of diplomacy in the settlement of island disputes by taking a case study of the disputed islands of Tiran and Sanafir between Saudi Arabia and Egypt. This research tries to apply the theory of diplomacy and state sovereignty in looking at protecting the territory from unilateral recognition from countries that try to dominate by force and seek cooperation when the state is under pressure. Through this research, the author finds that the dynamics of Saudi-Egyptian relations have experienced ups and downs in resolving disputes between the two islands and the diplomacy used by Saudi Arabia to take over its sovereignty again by means of bourgeois-civil diplomacy or commercial diplomacy, namely diplomacy that prioritizes profitable negotiation efforts both parties in a peaceful manner with supporting agreements in the economic, political and security fields.This research uses qualitative methods and descriptive and historical analysis with data collection techniques through literature studies sourced from several books, journals, articles and websites. This research uses the realism perspective and the theory of state sovereignty and diplomacy theory in analyzing the problems of the Tiran and Sanafir Islands dispute between Saudi Arabia and Egypt.The results of this study indicate that Saudi diplomacy in the settlement of the Tiran and Sanafir Islands dispute is using Bourgeois-Civil Diplomacy or Commercial Diplomacy, namely by negotiating compromise and peaceful means supported by cooperation agreements in the fields of security, economy and politics. The agreement is contained in the Agreement of Maritime Boundary Demarcation 2016 which was signed in Cairo. Keyword: Diplomacy, Dispute, Saudi Arabia, Egypt, Tiran and Sanafir